Genetic‐based design of a tetra‐band high‐efficiency radio‐frequency energy harvesting system. Issue 15 (1st December 2013) - Masotti, Diego; Costanzo, Alessandra; Del Prete, Massimo; Rizzoli, Vittorio
Abstract : In this study, we exploit genetic algorithms to design a rectenna required to harvest ambient radio‐frequency (RF) energy from four different RF bands in critical (ultra‐low power) conditions. For this purpose a set of multi‐resonant annular‐ring patch antennas are pixel‐wise described inside an electromagnetic simulator to provide the 'population' of individuals among which the genetic tool is able to select the most adapted one with respect to the design specifications. The further use of circuit‐level non‐linear simulation tool, based on Harmonic balance technique, allows the rigorous multi‐band design of the whole rectenna system in RF stationary conditions at several received power levels. The result is a novel compact, lightweight and highly efficient tetra‐band rectenna, able to harvest RF energy from GSM 900, GSM 1800, UMTS and WiFi sources available in the ambient. At these frequency bands high radiation efficiency is desired as an essential prerequisite for optimally handling very low‐power densities. Very good agreement with measurements of both the radiating and rectifying designs is demonstrated in real office scenarios. Finally the rectenna is connected to a power management unit and the resulting assembly is tested in terms of stored energy while harvesting from a mobile cell‐phone call.